ANTINEOPLASTIC AND ANTIOXIDANT ACTIVITIES OF ACORUS CALAMUS L ON SWISS ALBINO MICE BEARING DALTON’S ASCITES LYMPHOMA - SB, SREEJAYA; KS, SANTHY (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Ethnobotanical alternates for synthetic allopathic drugs are soon gaining importance in the treatment of diseases due to their fewer side effects. Acorus calamus has been widely used globally due its richness in antioxidant phytoconstituents in the treatments yielding beneficial functions. The present study details the in vivo anticancerous effect of A. calamus against Dalton's ascites lymphoma (DAL). Methods: The extract obtained by soxhlet extraction was screened for antioxidants by the enzymatic and non-enzymatic methods to indicate any inhibitory properties on DAL induced cells. Results: Soxhlet extraction using organic solvents and water revealed methanol to yield a maximum percentage of the crude extract that was stored for antioxidant and antineoplastic analysis. DAL induced tumor cells in mice revealed decreased levels of superoxide dismutase, catalase, glutathione peroxidise, glutathione, vitamin C and also vitamin E on analysis of liver and kidney samples. The same organs, when analyzed on treatment with the methanolic extract of A. calamus revealed a reversal of these decreased values to normal range. Conclusion: These results thus indicate the potential use of A. calamus for anticancer studies although the main phytoconstituent in the extract obtained is to be further analyzed. Keywords: Acorus calamus, Dalton's ascites lymphoma, Anticancer, Phytoconstituents, Antioxidants.